Synthesis, Characterization and Bioactivities of Some Novel Oxovanadium(IV) Glycinato Complexes - Islam, Mohammad K.; Nuruzzaman, Md.; Ripon, Rashedul I.; Shalauddin, Md.; Biswas, Foni B.; Hossain, Mamun M.; Islam, Mohammad R.; Khan, Sumaiya (European Scientific Journal, ESJ, 2018)
The novel oxovanadium(IV) complexes, [VIVO(GlyH)(Gly)]+ClO4 - .H2O (1), [VIVO(GlyH)(Gly)]+NO3 - .H2O (2), [VIVO(GlyH)(Gly)]+CH3COO- .H2O (3) were synthesized and characterized by FT-IR, UV-Vis and 1H NMR spectroscopic measurements. The cumulative spectroscopic assessment envisaged that, the complexes adopt a square pyramidal structure, in which the two glycine ligands coordinate to vanadium(IV) center in bidentate fashions conforming a homoleptic structure. The amino nitrogen and a carboxylato oxygen atom coordinate the vanadium(IV) center from both sides making a five members chelate by each side. All the complexes are stable in amorphous state and in aerobic and anaerobic solution. Significantly, all the complexes have the antifungal activities against Aspergillus niger and Penicillium notatum but ineffective against Candida tropicalis. No antibacterial activity was observed for the complexes against tested bacteria and unfortunately, they were found cytotoxic against brine shrimp bioassay.